Physicochemical Study on the Strength Development Characteristics of Cold Weather Concrete Using a Nitrite–Nitrate Based Accelerator - Heesup Choi (Materials, 2019)
There has recently been an increased use of anti-freezing agents that are primarily composed of salt- and alkali-free calcium nitrite (Ca(NO2)2) and calcium nitrate (Ca(NO3)2) to promote the hydration reaction of concrete in cold weather concreting. Nitrite−nitrate based accelerators accelerate the hydration of C3A and C3S in cement more quickly when their quantities are increased, thereby boosting the concrete’s early strength and effectively preventing early frost damage. However, the connection between the hydrate formation behavior and the strength development characteristic over time has yet to be clearly identified. Therefore, in this study, a wide range of physicochemical reviews were carried out to clarify the relationship between the hydrate formation behavior and the strength development characteristics, both at an early age and at later ages, which results from the addition of nitrite−nitrate based accelerators to concrete in varying amounts. These accelerators also act as anti-freezing agents. The results show that an increased quantity of nitrite−nitrate based accelerators caused an increase in the early strength of the concrete. This was due to the formation of nitrite and nitrate hydrates in large amounts, in addition to ettringite containing SO42, which is generated during the hydration reaction of normal Portland cement at an early age. On the other hand, at later ages, there was a rise in nitrite and nitrate hydrates with needle crystal structures exhibiting brittle fracture behavior. A decrease in C−S−H gel and Ca(OH)2 hydrates, deemed to have caused a decline in strength on Day 3 and thereafter, was also observed.